Nutritional Potential of Bambara Bean Protein Concentrate - Mune, Martin Alain Mune; Minka, Samuel Rene; Mbome, Israel Lape; Etoa, F.-X. (Pakistan Journal of Nutrition, 2011)
Bambara bean protein concentrate was prepared under optimum conditions previously determined. Concentrate yield (27.12%) and protein yield (84.35%) were high. The concentrate had 70.85% protein and 13.15% lipid. Water-soluble compounds were removed in abundance from the flour, during the protein extraction. Bambara bean protein concentrate had similar levels of Fe and Zn as the flour. Antinutritional factors were significantly (p<0.05) reduced in the concentrate. The concentrate showed significantly (p<0.05) higher protein digestibility than the flour and had balanced amino acids contents with respect to the FAO/WHO pattern. Lysine and leucine were the predominant essential amino acids. The protein extraction process removed sulphur- and tryptophan-rich proteins. This affected the chemical score (26.80%), protein digestibility corrected amino acid score (25.40%), essential amino acid index (60.44%) and calculated biological value (54.18%) of the protein concentrate, which were lower than those of the flour.